Primary and secondary prevention of preterm birth: a review of systematic reviews and ongoing randomized controlled trials. (May 2019) - Matei, Anca; Saccone, Gabriele; Vogel, Joshua P.; Armson, Anthony B.
Abstract: Background: Preterm birth (PTB) is a leading cause of perinatal morbidity and mortality. Interventions aimed at preventing PTB can be classified as primary, secondary, or tertiary prevention. Objective: To conduct a review of systematic reviews on the effectiveness and safety of primary and secondary preterm birth prevention interventions. Search strategy: A systematic literature search of the Cochrane, PubMed/Medline, EMBASE and CINAHL databases was conducted on 2 September 2015, and updated on 21 November 2016. Selection criteria: We included any published systematic review of randomized controlled trials (RCTs) or individual patient data (IPD) of RCTs related to primary or secondary prevention of PTB, published between 2005–2016 where gestational age at birth (of any interval) was a pre-specified outcome. Individual trials and non-systematic reviews were not eligible. Data collection and analysis: The population of interest was all pregnant women, regardless of PTB risk. The primary outcome was PTB < 37 weeks. Main Results: In total, 112 reviews were included in this study. Overall there were 49 Cochrane and 63 non-Cochrane reviews. Eight were individual participant data (IPD) reviews. Sixty reviews assessed the effect of primary prevention interventions on risk of PTB. Positive effects were reported for lifestyle and behavioural changes (including diet and exercise); nutritional supplements (including calcium and zinc supplementation); nutritional education; screening for lower genital tract infections. Eighty-three systematic reviews were identified relating to secondary PTB prevention interventions. Positive effects were found for low dose aspirin among women at risk of preeclampsia; clindamycin for treatment of bacterial vaginosis; treatment of vaginal candidiasis; progesterone in women with prior spontaneous PTB and in those with short midtrimester cervical length; L-arginine in women at risk for preeclampsia; levothyroxine among women with tyroid disease; calcium supplementation in women at risk of hypertensive disorders; smoking cessation; cervical length screening in women with history of PTB with placement of cerclage in those with short cervix; cervical pessary in singleton gestations with short cervix; and treatment of periodontal disease. Conclusion: The overview serves as a guide to current evidence relevant to PTB prevention. Only a few interventions have been demononstrated to be effective, including cerclage, progesterone, low dose aspirin, and lifestyle and behavioural changes. For several of the interventions evaluated, there was insufficient evidence to assess whether they were effective or not.